Relationship between ventilator-associated pneumonia and mortality in COVID-19 patients - Nseir, Saad (2021)
Funding: This study was supported in part by a grant from the French government through the «Programme Investissement d’Avenir» (I-SITE ULNE) managed by the Agence Nationale de la Recherche (coVAPid project). The funders of the study had no role in the study design, data collection, analysis, or interpreta tion, writing of the report, or decision to submit for publication.